Dangerous counterstories in the corporate academy : narrating for understanding, solidarity, resistance, and community in the age of neoliberalism - Daniels, Emily A.; Porfilio, Bradley J. (Critical constructions., 2013)
Although the social reality is stark for progressive scholars who engage in scholarly activities or are committed to guiding their students to develop a social-just praxis in the circles of higher education, some scholars have found fissures amid the alienating, often hostile academic world to learn, grow, and create transformative communities. Up to this date, however, their stories have not been captured. Therefore, the purpose of this volume is to highlight alternative narratives generated by transformative scholars who have maintained their oppositional identity to the structures that oppress the vast majority of citizens. By bringing together these narratives, we focus on those who have joined with likeminded colleagues to teach, engage in activism, and conduct emancipatory forms of research, learning to negotiate and survive academic and corporate realities in spite of restrictive climates.Not only are these stories vital for helping students, academics, and the wider community understand how commercialized forces are impacting the professional lives of critical scholars in the academy, they have the power to help current and future critical pedagogues define (and redefine) themselves in a social world which is continually 'promoting a narrow and intellectually stifling agenda for the role of education and turning the public against the very idea of a critical education' (McLaren, 2006). As stated by Bruner (1986) stories give 'a map of possible roles and possible worlds in which action, thought, and self-definition are possible (or desirable)' (p. 2, cited in Collins & Cooper, 2005). These possibilities for definition and redefinition are what we seek to present, explore and understand.